Socio-economic development of tribes in India - Thakur, Devendra (New Delhi : Deep & Deep Publications, 1986)
With special reference to Santals of Bihar.
Includes index.
Bibliography: p. [251]-257.
mizan
Keywords: Santal (South Asian people) -- Economic conditions; Rural development -- India; Bihar (India) -- Economic conditions